2015
DOI: 10.1016/j.molimm.2015.03.245
|View full text |Cite
|
Sign up to set email alerts
|

MBL-associated serine proteases (MASPs) and infectious diseases

Abstract: The lectin pathway of the complement system has a pivotal role in the defense against infectious organisms. After binding of mannan-binding lectin (MBL), ficolins or collectin 11 to carbohydrates or acetylated residues on pathogen surfaces, dimers of MBL-associated serine proteases 1 and 2 (MASP-1 and MASP-2) activate a proteolytic cascade, which culminates in the formation of the membrane attack complex and pathogen lysis. Alternative splicing of the pre-mRNA encoding MASP-1 results in two other products, MAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 199 publications
1
51
0
Order By: Relevance
“…MASP2 encodes a member of the peptidase S1 family of serine proteases and cleaves complement components C2 and C4 to generate C3 convertase in the lectin pathway of the complement system. Polymorphisms in MASP2 genes are associated with protein serum levels and functional activity and with susceptibility to or protection against infectious diseases65. Significantly higher MASP2 levels are found in children and adults with type 1 diabetes mellitus66.…”
Section: Discussionmentioning
confidence: 99%
“…MASP2 encodes a member of the peptidase S1 family of serine proteases and cleaves complement components C2 and C4 to generate C3 convertase in the lectin pathway of the complement system. Polymorphisms in MASP2 genes are associated with protein serum levels and functional activity and with susceptibility to or protection against infectious diseases65. Significantly higher MASP2 levels are found in children and adults with type 1 diabetes mellitus66.…”
Section: Discussionmentioning
confidence: 99%
“…As with human MASP1 , the transcript and predicted transcripts that encode the three MASP1 isoforms share the first 8 exons; thus, the cluster of variants noted in intron 2 is also present in intron 2 for all of these predicted transcripts. Genetic mutations resulting in human MASP1 deficiency are associated with infectious disease, and several intronic mutations leading to MASP1 deficiency have been identified, though none are identical to the associations found here (Ingels et al 2013; Beltrame et al 2015). Again, the relative similarity of the allele frequencies for the different loci suggests significant linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 48%
“…Again, the relative similarity of the allele frequencies for the different loci suggests significant linkage disequilibrium. It should be noted that mutations that inhibit the function of the MASPs (and complement-activating collagenous lectins) may also confer benefits: excess activation of complement can contribute to tissue damage or autoimmune disease, and decreased or more moderate levels of complement activity may therefore be beneficial in some scenarios (Beltrame et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Among these biological functions, complement activation is considered to be particularly important in protecting the body from infectious diseases [25,26] . Furthermore, it was found that complement factors were present in the lung which might activate complement system during bacterial infection [25,27] .…”
Section: Discussionmentioning
confidence: 99%
“…6 a). It is well known that microbes opsonized by complement are easily recognized by phagocytes, which express complement receptors on their surface, and consequently lead to increased phagocytosis [26] . In in vitro analysis, rhCL-K1 could increase phagocytosis of E. coli , but it did not enhance the phagocytosis of S. pneumoniae ( Fig.…”
Section: Discussionmentioning
confidence: 99%